2022
DOI: 10.48550/arxiv.2206.09725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The $abcd$ conjecture, uniform boundedness, and dynamical systems

Abstract: We survey Vojta's higher-dimensional generalizations of the abc conjecture and Szpiro's conjecture as well as recent developments that apply them to various problems in arithmetic dynamics. In particular, the "abcd conjecture" implies a dynamical analogue of a conjecture on the uniform boundedness of torsion points and a dynamical analogue of Lang's conjecture on lower bounds for canonical heights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For polynomials with integral coefficients, by using a simple divisibility argument, it can be shown that all preperiodic points have periods at most 2. For a number field K and c ∈ O K , a result in [4] implies that the set of preperiodic points of f c (x) is uniformly bounded depending only on D = [K : Q] (see also [22]). However, it is still interesting to find an explicit bound for the number of preperiodic points of an integral quadratic polynomial.…”
Section: Arithmetic Dynamics Of the Map Fmentioning
confidence: 99%
“…For polynomials with integral coefficients, by using a simple divisibility argument, it can be shown that all preperiodic points have periods at most 2. For a number field K and c ∈ O K , a result in [4] implies that the set of preperiodic points of f c (x) is uniformly bounded depending only on D = [K : Q] (see also [22]). However, it is still interesting to find an explicit bound for the number of preperiodic points of an integral quadratic polynomial.…”
Section: Arithmetic Dynamics Of the Map Fmentioning
confidence: 99%